2021
DOI: 10.3389/fpls.2021.791680
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Induction Impacts Behavior and Performance of a Pollinating Herbivore

Abstract: Flowering plants use volatiles to attract pollinators while deterring herbivores. Vegetative and floral traits may interact to affect insect behavior. Pollinator behavior is most likely influenced by leaf traits when larval stages interact with plants in different ways than adult stages, such as when larvae are leaf herbivores but adult moths visit flowers as pollinators. Here, we determine how leaf induction and corresponding volatile differences in induced plants influence behavior in adult moths and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Instead, we observed constitutive emissions of such compounds from Lin− O. harringtonii plants at significantly greater rates than those from Lin+ plants (figure 4a,c), but no evidence for induced increases in VOC emissions from Lin− plants during or after herbivory (figure 4b,d). Our randomized location of these plants in the greenhouse, combined with our recent measurement of the expected volatile responses in four Nicotiana species using the same methods [59] lends confidence to these conclusions. Similarly, the demonstration that leaf herbivory induces JA and phenolic accumulation in flower buds (but not seeds) of Oenothera biennis, with concomitant reduction of damage by moth larvae that eat buds (but not those that eat seeds) [57], suggested a mechanism for reduced performance of H. lineata larvae on living O. harringtonii plants (figure 3c).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Instead, we observed constitutive emissions of such compounds from Lin− O. harringtonii plants at significantly greater rates than those from Lin+ plants (figure 4a,c), but no evidence for induced increases in VOC emissions from Lin− plants during or after herbivory (figure 4b,d). Our randomized location of these plants in the greenhouse, combined with our recent measurement of the expected volatile responses in four Nicotiana species using the same methods [59] lends confidence to these conclusions. Similarly, the demonstration that leaf herbivory induces JA and phenolic accumulation in flower buds (but not seeds) of Oenothera biennis, with concomitant reduction of damage by moth larvae that eat buds (but not those that eat seeds) [57], suggested a mechanism for reduced performance of H. lineata larvae on living O. harringtonii plants (figure 3c).…”
Section: Discussionmentioning
confidence: 52%
“…Instead, we observed constitutive emissions of such compounds from Lin− O. harringtonii plants at significantly greater rates than those from Lin+ plants (figure 4 a,c ), but no evidence for induced increases in VOC emissions from Lin− plants during or after herbivory (figure 4 b,d ). Our randomized location of these plants in the greenhouse, combined with our recent measurement of the expected volatile responses in four Nicotiana species using the same methods [59] lends confidence to these conclusions.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Olfactory senses play a decisive role in this process. Insects can use a precise olfactory system to distinguish the odorants that attract or inhibit oviposition, so as to locate a suitable oviposition substrate [33,34]. Our study found that the egg-laying numbers of FHo were significantly lower than those of the same mating state FWT, regardless of whether they mate with MWT or MHo, suggesting that the egg-laying decisions of females were altered under conditions where the olfactory system is almost lost (Figure 5A).…”
Section: Discussionmentioning
confidence: 83%
“…Although stress-induced volatiles have been shown to deter foliar oviposition by tobacco hornworm ( Manduca sexta ) adults on tobacco plants, the same volatiles were also shown to attract foraging M. sexta adults to flowers and thus enhance pollination. 212 In agarwood ( Aquilaria sinensis ), GLVs released from seeds can attract Vespa hornets, which are important seed dispersers. Additionally, many of these volatiles are similar to those induced during foliar herbivory; this has been suggested to be a repurposing of plant defense to facilitate effective seed dispersal.…”
Section: The Role Of Vegetative Plant Volatiles In Biotic Interactionsmentioning
confidence: 99%